Attribution theory in EFL teacher’s resistance of using technology - Nur Kamilah (Universitas Ahmad Dahlan)
It is now a trend to research the teacher's perspectives of using technology in a language class. However, the reasons why teachers keep perspectives are not well studied. It is known in the view of naive psychology, that what a person regards something matters more than how it actually is. To view success or failure, it is very humane to make excuses or reasons for how it happened. In the case of teacher’s reluctance of using technology in a language class, the present study aimed at explaining what could have underlain their resistance to using technology in their language classes, especially from the view of attribution theory. The study applied a qualitative approach using the phenomenology research design. The participants of the study were three high school language teachers from Situbondo, Indonesia. Added to the researcher as the primary research instrument were the interview and field notes. The findings of the study indicate that teachers have personally considered their resistance as something stable and uncontrollable. They believe that they become resistant because they do not have control over their ability as they believe the younger fellows are gifted with the ability to use IT fluently in the classroom. The findings imply that teachers are reluctant to use technology in the class because they fear failure when using technology in the classroom. It suggests that the magnitude of teachers’ attribution could determine what they could achieve in their professional development.